2014
DOI: 10.5114/wiitm.2014.44254
|View full text |Cite
|
Sign up to set email alerts
|

A comparative cost analysis study of lobectomy performed via video-assisted thoracic surgery versus thoracotomy in Turkey.

Abstract: IntroductionCost analysis studies performed in western countries report that the overall cost of lobectomies performed via video-assisted thoracic surgery is similar to or less than those performed via thoracotomy. The situation may be different in a developing country.AimWe evaluated the cost differences of these two surgical methods.Material and methodsWe retrospectively reviewed the hospital records of 81 patients who underwent lobectomy either via video-assisted thoracic surgery (n = 32) or via thoracotomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…One hundred and sixty-nine reports of 145 studies met the predefined inclusion criteria and were included in the review. 9…”
Section: Resultsmentioning
confidence: 99%
“…One hundred and sixty-nine reports of 145 studies met the predefined inclusion criteria and were included in the review. 9…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a study reported by Alpay et al showed that VATS lobectomy costs were greater than costs from thoracotomy lobectomy. 14 The authors concluded that these findings may have resulted from lower bed fees and higher disposable instrument costs. The total cost of thoracoscopic versus open lobectomy was variable in the above studies.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the study performed by Alpay et al, lower bed and manpower costs with higher disposable instrument costs may explain the higher total hospital costs in the thoracoscopic group in our study despite the shorter hospital stays and anesthesia times. 14 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 it is evidently proven the mean duration of stay in hospital shorter but cost doing it of significantly higher in majority of studies. 24 This option not viable in majority of our patients. 25 VATS and RATS have advantage of less pain and lesser complication when it's done for non infective lung diseases.…”
mentioning
confidence: 99%